Judges’ perspectives on the use of modern standard Arabic versus vernacular in court proceedings - Almanasra, Majd; Alkhseilat, Abdullah; Haider , Ahmad S; Abu Issa, Hamzeh; Meqdad, Saad; Khater, Mohammad Nasr (Research Journal in Advanced Humanities, 2025)
The choice of language in courts greatly aids in facilitating clarity, accessibility and actual legitimacy of court action. Generally, in Arabic-speaking countries, MSA is thought to be the standard formal language of law, while vernacular Arabic is the everyday spoken colloquial variety. The current study examines judges’ attitudes regarding the choice between the MSA and vernacular Arabic in court in terms of clarity and comprehensibility, formality, accessibility for the litigants, and regulatory issues. A well-designed 20-item questionnaire was distributed among 300 judges of different ranks (First Instance, Appeal, and Supreme/High Courts) operating in different geographical settings (urban, rural, and mixed) in Jordan. The results demonstrated that judges preferred MSA, strongly linking it with clarity, consistency, and authority in court, while vernacular Arabic was believed to help litigants and low educational background individuals understand the court procedures better. It is recommended that MSA should continue to be the language of record in order not to compromise institutional legitimacy, while it advocates the limited conscious use of vernacular Arabic during oral hearings in a way promoting fairness and encouraging participation.